KOMODIFIKASI BUDAYA DI ERA EKONOMI GLOBAL TERHADAP KEARIFAN LOKAL: Studi Kasus Eksistensi Industri Pariwisata dan Kesenian Tradisional di Jawa Tengah - Irianto, Agus Maladi (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2016)
Abstract: The culture commodification is the sale-purchase transaction of cultural objects through industrial process that was born along with the globalization era. The tourism industry is the child of globalization that produce cultural objects to be traded for the financial benefit. One form of the commodification cultural objects in the globalization era is the traditional arts. The problem is how the strategy needs to be developed so that the traditional arts as the subject of its supporting society's local wisdom is remain protected, but on the other hand it is expected to accomodate the demand of economic globalization that has conducted the culture commodification? With the aim to synergize the presence of traditional arts as the cultural identity of its supporting society and the tourism industry demands that conduct culture commo¬dification, then through a field research using qualitative method, it resulted the following description. First, the culture commo¬dification becomes a necessity in the global economy era that evolve in this era of postmodernity, especially it's marked by the growing of the tourism industry. Second, the culture commo¬dification to the local wisdom can basically be solved by several strategies without marginalizing the supporting society of the local wisdom. Third, the existence of traditional arts as a cultural identity can be protected and revitalized from the demands of the culture commodification, as long as it is also developing a concept that is able to synergize the perception and responses of the supporting society to the demands of the tourism industry. Fourth, one of the most relevant concepts to accommodate the demands of the culture com¬modification is a concept that is commonly referred as the pseudo traditional art. Abstrak: Komodifikasi budaya adalah transaksi jual beli benda budaya melalui proses industri yang lahir seiring dengan era globalisasi. Industri pariwisata adalah anak kandung globalisasi yang memproduksi benda budaya untuk diperjualbelikan demi keuntungan secara finansial. Salah satu bentuk benda budaya yang dikomodifikasi di era globalisasi adalah kesenian tradisional. Permasalahannya adalah, bagaimana strategi yang perlu dikembangkan agar kesenian tradisional sebagai subjek kearifan lokal masyarakat pendukungnya tetap telindungi, tetapi di sisi lain ia diharapkan bisa mengakomodasi tuntutan globalisasi ekonomi yang telah melakukan komodifikasi budaya? Dengan tujuan untuk mensinergikan antara keberadaan kesenian tradisional sebagai identitas kultural masyarakat pendukung dan tuntutan industri pariwisata yang melakukan komodifikasi budaya, maka melalui penelitian lapangan yang menggunakan metode kualitatif telah menghasilkan gambaran sebagai berikut. Pertama, komodifikasi budaya menjadi keniscayaan di era ekonomi global yang berkembang di era pascamodernitas ini, terutama ditandai dengan kian berkembangnya industri pariwisata. Kedua, komodifikasi budaya terhadap kearifan lokal pada dasarnya dapat dipecahkan dengan sejumlah strategi tanpa harus memarjinalkan masyarakat pendukung kearifan lokal tersebut. Ketiga, keberadaan kesenian tradisional sebagai identitas kultural dapat terlindungi dan direvitalisasi dari tuntutan komodifikasi budaya, sepanjang dikembangkan suatu konsep yang mampu mensinergikan antara persepsi dan respons masyarakat pendukung dengan tuntutan industri pariwisata. Keempat, salah satu konsep yang paling relevan untuk mengakomodasi tuntutan komodifikasi budaya adalah konsep yang lazim disebut sebagai psedo traditional art.